2011
DOI: 10.1016/j.cell.2011.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine 3-Monooxygenase Inhibition in Blood Ameliorates Neurodegeneration

Abstract: SUMMARY Metabolites in the kynurenine pathway of tryptophan degradation are thought to play an important role in neurodegenerative disorders such as Alzheimer’s disease and Huntington’s disease. Metabolites that cause glutamate receptor-mediated excitotoxicity and free radical formation are elevated in the blood and vulnerable brain regions in these diseases, while levels of the neuroprotective metabolite kynurenic acid are often decreased. Here we describe the synthesis and characterization of JM6, a novel sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
434
5
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(458 citation statements)
references
References 54 publications
12
434
5
7
Order By: Relevance
“…Kynurenine enzymes are being pursued as clinical targets for neurodegenerative and inflammatory disease, with at least two studies reporting that pharmacological inhibitors improve cognition (Pocivavsek et al ., 2011; Zwilling et al ., 2011). Mechanistic differences between branches of the kynurenine pathway are directly relevant to age‐associated disease in humans, where the dominant pathway branch varies by cell and tissue type (Schwarcz et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Kynurenine enzymes are being pursued as clinical targets for neurodegenerative and inflammatory disease, with at least two studies reporting that pharmacological inhibitors improve cognition (Pocivavsek et al ., 2011; Zwilling et al ., 2011). Mechanistic differences between branches of the kynurenine pathway are directly relevant to age‐associated disease in humans, where the dominant pathway branch varies by cell and tissue type (Schwarcz et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Kyn, KYNA (one branch of Kyn metabolism), 3-hydroxykynurenine, and quinolinic acid (another branch of Kyn metabolism) are all neuroactive compounds that play important roles in neurodegenerative disorders, including Alzheimer's and Huntington's diseases (Schwarcz et al, 1983;Foster et al, 1984;Sas et al, 2007). Recently, the augmentation of the KYNA-to-3-hydroxykynurenine ratio by genetic or pharmacological approaches was shown to have potential therapeutic benefits in both fly and mouse Huntington's disease models (Campesan et al, 2011;Zwilling et al, 2011). However, it has been reported that most core enzymes in Kyn metabolism could not be found in the Arabidopsis genome (Katoh and Hashimoto, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia produce quinolinic acid (QA), a selective NMDAR agonist and a metabolite of the tryptophan degradation pathway, that elicits symptoms reminiscent of HD when injected into the striatum, and symptoms similar to AD when injected into the nucleus basalis of rodents 35 . A recent study furthermore demonstrates that inhibiting kynurenine 3-monooxygenase, an enzyme in the pathway generating QA, can ameliorate excitotoxicity and disease phenotypes in mouse models of both AD and HD 35 .…”
Section: Non-neuronal Contributions To Excitotoxic Pathwaysmentioning
confidence: 99%
“…Alterations in microglial tryptophan metabolism, leading to increased release of neurotoxic metabolites 5,14,35 Neurotrophic factor related abnormalities…”
Section: Supplementary Materialsmentioning
confidence: 99%